1980
DOI: 10.1021/jm00175a013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and pharmacology of 8-amino-3-(cyclopropylmethyl)-1,2,3,4,5,6-hexahydro-cis-6,11-dimethyl-2,6-methano-3-benzazocine and related compounds

Abstract: The little compound 1a has been prepared and was found to be a strong, orally active agonist with narcotic--antagonist properties. 1a was prepared by two independent routes: (1) nitration of volazocine and subsequent reduction and (b) a sequence involving dissolving metal reduction of cyclazocine methyl ether, followed by oximination and Semmler--Wolff rearrangement. Several analogues were prepared and tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 0 publications
0
27
1
Order By: Relevance
“…These findings may explain why 8-CAC had a 10-fold lower ED 50 value than cyclazocine in the writhing assay. An earlier study showed that 8-amino-cyclazocine had an oral-to-parental ratio that was considerably better than the ratio observed with cyclazocine, suggesting that replacement of the 8-OH with a group that might not be metabolized as rapidly may increase the bioavailability of these compounds (Wentland et al, 1980). Future studies will address the bioavailability of 8-CAC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings may explain why 8-CAC had a 10-fold lower ED 50 value than cyclazocine in the writhing assay. An earlier study showed that 8-amino-cyclazocine had an oral-to-parental ratio that was considerably better than the ratio observed with cyclazocine, suggesting that replacement of the 8-OH with a group that might not be metabolized as rapidly may increase the bioavailability of these compounds (Wentland et al, 1980). Future studies will address the bioavailability of 8-CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclazocine is O-glucuronidated in humans, which may account for its short duration of action (Wentland et al, 1980). In an attempt to retard this metabolic inactivation and increase its duration of action, we discovered that replacement of the 8-OH group in cyclazocine with an 8-NH 2 provided a novel compound, 8-aminocyclazocine, which had somewhat diminished antinociception potency in mice when delivered by the subcutaneous route but comparable with cyclazocine efficacy when delivered orally (Wentland et al, 1980).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Glucuronidation of cyclazocine may account for its short duration of action 13. In an attempt to retard metabolism and increase the duration of activity, the 8‐OH group of cyclazocine was replaced with a NH 2 group 13. The replacement of the 8‐OH with an 8‐NH 2 increased the bioavailability of the compound.…”
Section: Introductionmentioning
confidence: 99%
“…Ligands in the neutral and protonated forms, as well as in the complexes (associates) [27] 3.9 b [27] n/a [27] II (methadone) l.6 b [28] III (naloxone) 60 a [27] 0.008 e [27] 0.08 f [29] IV (naltrexone) n/a [32] 0.05 f [27] V: R=OH (cyclazocine) 0.1 a [28] 0.04 a [31] 0.019 g [28] 0 > 10 g [28] n/a f [35] XI: R=CH 2 CH 2 CH 3 (N-propylnormethazocine) 3.9 a [35] n/a f [35] 0.019 g [29] XII: R=CH 2 -CH=CH 2 (N-allylnormethazocine) n/a b [30] 0.047 g [29] XIII: R=CH 2 -CH=C(CH 3 ); * agonist activity relative to pentazocine (ED 50 c = 120 mg/kg [33]); ED 50 is the dose producing analgesic action in 50% of test animals; AD 50 is the dose decreasing by half the analgesic action of an agonist administered in the ED 50 .…”
mentioning
confidence: 99%